2020
DOI: 10.1177/0260106020960990
|View full text |Cite
|
Sign up to set email alerts
|

Weight discordant siblings’ ability to reduce energy intake at a meal as compensation for prior energy intake from sugar-sweetened beverages (SSBs)

Abstract: Background: Insufficient compensation for energy from sugar-sweetened beverages (SSBs) consumed prior to meals may promote greater overall energy intake. If so, ability to compensate for prior energy intake may account for difference in adiposity between adolescents with and without overweight. Studies of fraternal siblings discordant for weight status control for some genetic and shared within-family factors, which allows for testing how putative non-shared factors, such as parental control of feeding, predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…However, in multiple regression analyses, differences in perceived restriction were not associated with differences in sibling weight. Several other studies also found non-significant relationships between parental use of restriction (Berge, Meyer, et al, 2016;Keller et al, 2006;Roemmich et al, 2010;Ufholz et al, 2020) or control (Berge, Tate, et al, 2016) and differences in sibling weight.…”
Section: Restriction or Controlmentioning
confidence: 91%
See 4 more Smart Citations
“…However, in multiple regression analyses, differences in perceived restriction were not associated with differences in sibling weight. Several other studies also found non-significant relationships between parental use of restriction (Berge, Meyer, et al, 2016;Keller et al, 2006;Roemmich et al, 2010;Ufholz et al, 2020) or control (Berge, Tate, et al, 2016) and differences in sibling weight.…”
Section: Restriction or Controlmentioning
confidence: 91%
“…Similarly, parents used more pressure toward the sibling with a lower inherited susceptibility to a higher BMI (defined by a lower BMI genome-wide polygenic score) (Selzam et al, 2018). In one study, however, the use of differential pressure to eat was only evident in siblings who were discordant on weight status (healthy weight vs. overweight) (Berge, Tate, et al, 2016) and in three studies, no differences in parental pressure to eat were reported despite differences in sibling weight (Berge, Meyer, et al, 2016;Roemmich et al, 2010;Ufholz et al, 2020).…”
Section: Pressure To Eatmentioning
confidence: 96%
See 3 more Smart Citations